Production of a Novel Killer Toxin from Saccharomyces Eubayanus Using Agro-Industrial Waste and Its Application Against Wine Spoilage Yeasts - Ganga-Munoz, M (Springer Netherlands, 2019)
The juicing industry generates large amounts of waste that mostly lack commercial value and, in the absence of waste treatment policies, produces environmental pollution. Also, microbiological spoilage is a major concern in the wine industry and control tools are limited. Taking these challenges into account, agro-industrial waste coming from ultrafiltrated apple and pear juice were used to grow Saccharomyces eubayanus and to produce its killer toxin (SeKT). A Plackett–Burman screening was performed in order to optimize SeKT production in ultrafiltrated apple and pear juice. The optimized medium was characterized: 75% v/v WUJ, 0.5% m/v KH2PO4, 0.5% m/v MgSO4, 0.5% m/v (NH4)SO4, 0.5% g/L urea, 10% v/v glycerol and 0.1% v/v Triton X-100. SeKT produced in WUJ optimised medium was used to perform killer assays against wine spoilage yeasts and showed antagonistic activity against Brettanomyces bruxellensis, Pichia guilliermondii, Pichia manshurica and Pichia membranifaciens. Different inhibition percentages against spoilage species in a wine environment (49–69%) were detected and preserved for at least 48 h. For the first time, this work reports the ability of S. eubayanus to produce a killer toxin with potential use as a biocontrol tool in winemaking. Producing SeKT using agro-industrial waste as an alternative medium to cultivate S. eubayanus would have industrial, economic and ecological benefits. © 2019, Springer Nature Switzerland AG.